212k views
4 votes
If 5 times the 5th term of an ap is equal to 8 times the 8th term show that its 13th term is zero

User Freeman
by
5.1k points

1 Answer

2 votes

Answer:

Proved below

Explanation:

Given that


5a_(5)=8a_(8) .......(1

as we know


a_(5)= a_(1) + 4d


a_(8)= a_(1) + 7d

where d is the common difference. So, equation (1) would become


5(a_(1) + 4d)=8(a_(1) + 7d)


5a_(1) + 20d=8a_(1) + 56d

Rearranging


5a_(1) - 8a_(1)=-20d + 56d


- 3a_(1)=36d

So,


a_(1)=-12d .....(2)

As we know


a_(13)= a_(1) + 12d ......(3)

So, substituting the value of a1 into equation (3)


a_(13)= -12d + 12d


a_(13)= 0

Hence Proved

User Tomas Gonzalez
by
5.7k points